'And from his side came blood and milk': the martyrdom of St Philotheus of Antioch in Coptic Egypt - Rogozhina, A (2015)
My thesis examines the function and development of the cult of saints in Coptic Egypt. For this purpose I focus primarily on the material provided by the texts forming the Coptic hagiographical tradition of the early Christian martyr Philotheus of Antioch, and more specifically - the Martyrdom of St Philotheus of Antioch (Pierpont Morgan M583). This Martyrdom is a reflection of a once flourishing cult which is attested in Egypt by rich textual and material evidence. This text enjoyed great popularity not only in Egypt, but also in other countries of the Christian East, since his dossier includes texts in Coptic, Georgian, Ethiopic, and Arabic. This thesis examines the literary and historical background of the Martyrdom of Philotheus and similar hagiographical texts. It also explores the goals and concerns of the authors and editors of Coptic martyr passions and their intended audience. I am arguing that these texts were produced in order to perform multiple functions: to justify and promote the cult of a particular saint, as an educational tool, and as an important structural element of liturgical celebrations in honour of the saint. Another aim of this work is to stress the entertainment value of such texts. I explore the sources used by Coptic hagiographers for creating such entertaining stories, as well as the methods they used to re-work certain theological concepts and make them more accessible to the audience. The thesis begins with description of the manuscript tradition of Philotheus and a brief outline and comparison of its main versions. The second chapter discusses the place of the Martyrdom of Philotheus in Coptic hagiography and its connection to the so-called cycles. The next two chapters explore the motifs and topoi characteristic of Coptic martyr passions, especially the legend of Diocletian the Persecutor and the image of Antioch as the Holy City in Coptic hagiography, as these two motifs appear in one way or another in the majority of the martyr passions. Chapter 5 is dedicated to one of the focal points in the Martyrdom - the miracle of resurrection and the tour of hell – and its literary and theological background. Chapter 6 discusses representations of magic and paganism in Coptic hagiography and some of the concerns of Coptic hagiographers. In the last chapter I explore the geography of the cult, its iconographic and hymnographic dimensions and the transformation of the perception of the saint; the second part of this chapter discusses the questions of performance, authorship and audience.